Tectonic evolution of the Aravalli orogen (NW India): an inverted Proterozoic rift basin? - Verma, Pramod Kumar; Greiling, Reinhard O. (Geologische Rundschau, 1995)
The Aravalli mountain range (AMR) in the northwestern part of the Indian Peninsula consists of two main Proterozoic metasedimentary and metaigneous sequences, the Aravalli and Delhi Supergroups, respectively, which rest over the Archaean gneissic basement. A synthesis and reinterpretation of the available geological, geochronological and geophysical data, including results of own field work and geophysical interpretations pertaining to the AMR, indicate its origin as an inverted basin: rifting into granitoid basement began ca. 2.5; Ga ago with Aravalli passive rifting (ca. 2.5-2.0 Ga) and Delhi active rifting (ca. 1.9-1.6 Ga). Associated mafic igneous rocks show both continental and oceanic tholeiitic geochemistry and are comparable with Phanerozoic, rift-related magmatic products. Available data showed no conclusive evidence for oceanic lithoshere and island-arc/active margin magmatic activity in the AMR. Subsequent inversion and orogeny (Delhi orogeny, ca. 1.5-1.4 Ga) lead to complex deformation and metamorphism. Only in the western and central zones has the basement been involved in this mid-Proterozoic (Delhi) deformation, whereas it is unaffected in the eastern part, except for local shear zones mainly along the basement/cover interface. The grade of metamorphism increases from the greenschist facies in the east to the amphibolite facies in the west with local HP assemblages. These latter are explained by rapid burial and exhumation of thin and cool continental lithosphere. Subsequently, during a final, mild phase of inversion, the Vindhyan basins consisting mainly of sandstones, limestones and shales, flanking the AMR formed which are comparable to foreland basins. The tectonic evolution of the AMR is therefore interpreted as an example of a major inverted continental rift and of a Proterozoic intra-continental orogen.
Gesehen am 16.01.2023